Peran Media Sosial Tiktok Dalam Membentuk Perilaku Politik Generasi Z: Systematic Literature Review - Ariel Kurniawan Hardiansyah; Intana Sinthia Dewi; Nadina Melati; Nova Anisa; Khoiriya Ulfah (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2026)
This study aims to systematically analyze the role of the social media platform TikTok in shaping the political behavior of Generation Z in Indonesia, particularly during the 2024 General Election. The study employs a Systematic Literature Review (SLR) method using the PRISMA approach by analyzing 19 scientific articles published between 2021 and 2026 in various national and international journals. The findings indicate that TikTok has become one of the main platforms for political campaigns, influencing political participation, candidate perceptions, and the behavior of first-time voters among Generation Z. TikTok’s algorithm, short-form video content, live-streaming features, and high virality potential have proven effective in increasing political engagement. However, the use of TikTok in politics also presents risks such as manipulative information, digital polarization, and dependence on algorithms. This study is expected to contribute to understanding the impact of digital media on democracy in Indonesia.